Influencing factors and configuration pathways of fundraising effectiveness in charitable foundations: An FSQCA analysis of 54 cases in China - Zhe Zhu; Shan Huang; Wanqiang Xu; Heran Zou (PLoS ONE, 2026)
Charitable foundations play an important role in assisting vulnerable groups, narrowing the wealth gap, and addressing challenges such as urban-rural and regional development imbalances. Unlike other nonprofit organizations, fundraising effectiveness serves as a vital lifeline for the sustainable and stable development of charitable foundations. This study analyzed 54 Chinese charitable foundations and employed the fsQCA method to explore the factors influencing their fundraising effectiveness and their configuration effects. Research has found that: (1) digital transparency infrastructure and program activity intensity are key conditions for improving the fundraising effectiveness of charitable foundations; the level of professional management and political connections exert important impacts on enhancing the fundraising effectiveness of foundations, serving as important influencing conditions for the improvement of fundraising effectiveness. (2) There are two core paths for charitable foundations to achieve high fundraising benefits: one is a combination of strong program activity, robust digital transparency, and high political connections; the other is a combination of strong program activity, robust digital transparency, and high professional management. This study enriches and expands the theoretical connotation and research paradigm of charitable fundraising research and provides empirical evidence and policy guidance for promoting the sustainable and healthy development of charitable foundations.